Investigation of adhesion property and superhydrophobicity of silica/PDMS coating from electrophoretic deposition on 316 stainless steel substrate - De Juan, Lyn Marie Z. (College of Engineering, University of the Philippines Diliman, 2014)
Stainless steel 316 is known for its corrosion resistant property, but stretching and folding can damage the passivation layer which makes it less resistant to corrosion. Coating it with a superhydrophobic film with good adhesion property can enhance its water repellent ability and further improve its corrosion resistant property. Though there are numerous studies about superhydrophobic coatings, their adhesion property to their substrate is usually neglected. This study aims to produce a superhydrophobic coating with good/acceptable adhesion/shear strength property on stainless steel substrate. In this study, the effects of the deposition time, pH, and the amount of silica, Vinyl Terminated Dimethylsiloxane (DMS), and (3-4% Methylhydrosiloxane)-dimethylsiloxane co-polymer Trimethylsiloxane terminated (HMS) of the Electrophoretic Deposition (EPD) suspension on the produced coating were determined. It was found that the exposed substrate was completely covered after 5 minutes deposition time and an increase in deposition time to 10 minutes resulted to microcracks. It was also found that though use of basic suspension at pH 12 yielded the highest contact angle, the same condition resulted to very poor adhesion while the solution was still wet and resulted to incomplete coating coverage when the sample was air dried vertically. On the other hand, if the EPD was performed at pH 3.61 to pH 11.04, a hydrophilic coating was obtained due to the absence of HMS which was deposited at the counter electrode as indicated by the Fourier Transform Infrared - Attenuated Total Reflectance (FTIR-ATR) analysis. However, at acidic condition, it was observed that high contact angle was obtained with better adhesion property, and thus the best condition was found to be under pH 0.86. A 2^3 factorial experiment was performed in order to determine the necessary amount of each component in order to produce a superhydrophobic coating with acceptable adhesion property/shear strength. Based on the statistical analysis of the water contact angle, the effects of C (silica), AB (DMS-HMS) interaction, and BC (HMS-silica) interaction are significant at the 95% confidence level. An increase in the amount of silica resulted to a lower contact angle due to larger deposited aggregates that reduces the surface nanoroughness as shown by the surface morphology images taken using the Scanning Electron Microscopy (SEM). Based on the FTIR-ATR analysis, an increase in the amount of silica increases the intensity peak of the Si-O-Si stretch that indicates that higher amount of silica was present at the surface of the produced coating which can also reduce the measured contact angle. On the other hand, the interaction plots of both AB and BC show anti-synergistic effects. Based on the interaction plot of AB, at low DMS content, the effect is negative. The combination of low DMS and high HMS actually yields the highest contact angle in the plot. The interaction plot of BC shows that at low HMS content the effect of increasing silica is negative (contact angle decreases) while at high HMS content, the effect is slightly positive. The best combination for highest contact angle corresponds to the low HMS and low silica settings. The results of shear testing to estimate the adhesion strength or average maximum shear strength (thereby shortened to adhesion/shear strength) of the coating revealed that treatment combination (1), with low setting of all the EPD suspension components, yielded the highest adhesion/shear strength, while treatment combinations with high amount of HMS resulted to an acceptable adhesion/shear strength, i.e. higher than or equal to the adhesion/shear strength of cyanoacrylate adhesive that delaminates at the substrate-coating interface. On the other hand, high amount of DMS and/or silica resulted to very low adhesion/shear strength, i.e. less than the detectable limit, wherein delamintaion occurs in the coating which means that the deposit-deposit interaction was weaker that the deposit-substrate interaction. It was observed under FTIR-ATR analysis that all the produced coatings have the same peaks as that of the pristine poly-Dimethylsiloxane (PDMS) which indicates that PDMS was formed. The high adhesion/shear strength of treatment combination (1) was due to the absence of the deformation peaks, such as CH3 asymmetric deform, CH3 symmetric deform, and Si-O-Si asymmetric deform, and the presence of ketone bearing methoxy group. A statistical analysis for the adhesion/shear strength revealed that only the main effect of silica was significant at the 90% confidence level considering the interaction effects as estimates of the experimental error. When the ratio of DMS/silica was considered as a combined factor, the adhesion/shear strength appeared to follow a parabolic trend whose maximum was at 4.5 DMS/silica ratio. Low amount of silica resulted to low adhesion strength due to the insufficient amount of PDMS at the substrate-coating interface that binds the produced coating on the surface of stainless steel. On the other hand, further increase in the amount of DMS beyond 4.5 DMS/silica ration appears to lower the adhesion strength due to lesser amount of fillers that strenghten the produced coating. It was observed that the best condition in the study was treatment combination (1) with low settings for all factors producing an acceptable contact angle of 150° and good adhesion strength/shear strength at 20MPa.